1990
DOI: 10.1007/bf00858632
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of percutaneous renal biopsy in children: an analysis of 120 consecutive cases

Abstract: One hundred and twenty percutaneous renal biopsies performed in 104 patients aged 1 month to 15 years were analysed. Ultrasound examination was used for localization of the kidneys. Adequate renal tissue was obtained in 103 biopsies, with an overall success rate of 85.8%. The most frequent complication was gross haematuria, which occurred in 32 biopsies, but only 5 children required blood transfusion. Nineteen patients developed perirenal haematoma; 2 of these were symptomatic. Arteriovenous fistula was diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 23 publications
3
28
1
Order By: Relevance
“…To our knowledge, the current study is the only nationwide registry-based and largest report of renal biopsy complications, and our findings confirm the general impression of low complication rates and improved safety of modern renal biopsy procedures (19). Similar low complication rates have been reported in recent studies (16,19,20) in contrast to earlier studies (reporting 5%-7% complication rates) (21)(22)(23)(24)(25). The crucial safety evaluation of kidney biopsies is characterized by the overall risk and frequency of major complications, which in our study, are defined as need of blood transfusion and/or surgery or catheterbased intervention (embolization) secondary to bleeding, and they should not be jeopardized by procedural events of minor clinical relevance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, the current study is the only nationwide registry-based and largest report of renal biopsy complications, and our findings confirm the general impression of low complication rates and improved safety of modern renal biopsy procedures (19). Similar low complication rates have been reported in recent studies (16,19,20) in contrast to earlier studies (reporting 5%-7% complication rates) (21)(22)(23)(24)(25). The crucial safety evaluation of kidney biopsies is characterized by the overall risk and frequency of major complications, which in our study, are defined as need of blood transfusion and/or surgery or catheterbased intervention (embolization) secondary to bleeding, and they should not be jeopardized by procedural events of minor clinical relevance.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the relative risk was 16 times higher when eGFR was below 30 ml/min per 1.73 m 2 (Table 4). Although elevated risk has been shown previously, the increased risk incurred by kidney failure may be underscored in many reports (14,21,33,34), and the work by Whittier and Korbet (25) found that serious complications were about two times as common in patients with serum creatinine above 5.0 mg/dl. It is conceivable that this observation is associated with the general increased bleeding tendency seen in kidney failure patients (33).…”
Section: Discussionmentioning
confidence: 94%
“…As noted above, immediate post-biopsy images are also obtained by ultrasound to assess for hematoma formation and to provide a postbiopsy baseline. Others employ routine post-biopsy ultrasound from 24 hours to two weeks following renal biopsy in all patients to detect peri/intra renal hematoma formation with consideration of Doppler studies to assess for arteriovenous fistula formation (Al Rasheed et al, 1990;Kamitsuji et al, 1999;Mahajan et al, 2010), though it is unclear whether this changes clinical care of the stable patient (Castoldi et al, 1994). It is also our practice to observe patients for at least 6 to 8 hours post-procedure and to check a hemoglobin and hematocrit level at 4-6 hours post biopsy and again the next morning as long as there is no concern to warrant repeat laboratory work sooner.…”
Section: Post-biopsy Monitoring In Childrenmentioning
confidence: 99%
“…Death is extremely rare. One early review (Al Rasheed et al, 1990, as cited in White, 1963 reported 17 deaths in more than 10,000 biopsies (0.17%). Similarly, another large review at that time reported a mortality rate of 0.12% in 4000 biopsies (Simckes et al, 2000, as cited in Dodge et al, 1962.…”
Section: Minor Complications Major Complicationsmentioning
confidence: 99%
See 1 more Smart Citation